PENGARUH ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN DAN KEUNGGULAN BERSAING TERHADAP KINERJA PEMASARAN PEMBUAT KOPI KAHIANGA DI WAKATOBI - La Ode Azaluddin Siga; Patwayati Patwayati; Hayat Yusuf; Juharsah Juharsah; Hartini Hartini (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study aims to test and analyze: (1). To determine and analyze the effect of market orientation on the marketing performance of the Kahianga Coffee maker business in Wakatobi, (2). To find out and analyze the effect of entrepreneurial orientation on the marketing performance of the Kahianga Coffee maker business in Wakatobi and (3). To find out and analyze the effect of competitive advantage on the marketing performance of the Kahianga Coffee maker business in Wakatobi. This study used 50 respondents who made kahianga coffee in Wakatobi. While the data analysis used descriptive analysis and inferential analysis of Multiple Linear Regression using the program packagesoftware SPSS Version 24.0.The results of this study are (1).Market orientation has a positive and significant effect on the marketing performance of kahianga coffee makers in Wakatobi, (2). Entrepreneurial orientation has a positive and significant effect on the marketing performance of kahianga coffee makers in Wakatobi, and (3)Competitive advantage has a positive and significant impact on the marketing performance of kahianga coffee makers in Wakatobi.